2019
DOI: 10.3390/md17040221
|View full text |Cite
|
Sign up to set email alerts
|

Marine-Derived Natural Compounds for the Treatment of Parkinson’s Disease

Abstract: Parkinson’s disease (PD) is a neurodegenerative disorder caused by the loss of dopaminergic neurons, leading to the motor dysfunctions of patients. Although the etiology of PD is still unclear, the death of dopaminergic neurons during PD progress was revealed to be associated with the abnormal aggregation of α-synuclein, the elevation of oxidative stress, the dysfunction of mitochondrial functions, and the increase of neuroinflammation. However, current anti-PD therapies could only produce symptom-relieving ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 134 publications
1
36
0
Order By: Relevance
“…To date, only a few marine fungal metabolites are known to be neuroprotective [24]. Neoechinulin A is well known for its antioxidant properties [35].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, only a few marine fungal metabolites are known to be neuroprotective [24]. Neoechinulin A is well known for its antioxidant properties [35].…”
Section: Discussionmentioning
confidence: 99%
“…Reactive oxygen species cause serious damage and death of dopamine-producing cells when the antioxidant capacity of the cell is reduced against oxidative stress [22,23]. For this reason, compounds may be very effective in treating PD based on in vitro and in vivo models if they demonstrated free radical scavenger effects in cell-free assays or anti-ROS influences in cell-based tests [24].…”
Section: Biological Activities Of the Isolated Compoundsmentioning
confidence: 99%
“…Over the last decade, some excellent works reviewed the neuroprotective effects of marine algae and their metabolites [ 21 , 22 , 23 , 29 , 33 , 34 , 35 ]. However, some of these reviews limited their scope either to a single pathogenic mechanism such as neuroinflammation [ 22 ] or to categorical brain disorders such as AD or PD [ 22 , 23 , 29 , 34 , 35 ]. Others have reviewed literature published a decade or half a decade ago [ 23 , 36 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several plants derived compounds such as brown rice (Chompoopong et al, 2016), cinnamaldehyde (Mehraein et al, 2018), pepper (Ogunruku et al, 2019) and drugs such as Ceftriaxone (Ruzza et al, 2014;Ho et al, 2014), piracetam (Verma et al, 2015) were proved to be effective in treating dementia in experimental PD. Marine-derived natural products such as omega-3-fatty acid, inosine, etc., were currently under clinical trials against PD (Huang et al, 2019). Moreover, Ho et al (2011) revealed that D-cycloserine was advantageous in the management of biochemical, biological detrimental changes in experimental PD, including cognitive disorders, motor dysfunction.…”
Section: Discussionmentioning
confidence: 99%